Біологічні особливості видів вічнозелених листяних кущів, інтродукованих на південний схід України - Шапарєва, М.О. (Промышленная ботаника, 2013)
Исследованы особенности сезонного роста и развития 10 видов вечнозеленых лиственных кустарников, интродуцированных на юго-восток Украины. Они объединены в феногруппы, дана оценка их зимостойкости. Из исследованных видов выделено 8 перспективных для использования в озеленении городов юго-востока Украины. Features of the seasonal growth and development of 10 angiosperm evergreen shrub species introduced in the southeast of Ukraine were investigated. These species were divided in phenological groups and their winter hardiness was estimated. Eight out of all investigated species were selected as having potential for urban landscaping in the south-east of Ukraine.